BUSINESS MODEL COMPLEMENTARITY AND THE FACTORS THAT DETERMINE IT IN TOURISM BUSINESS FORMATIONS: THE THEORETICAL ASPECT - Kinderis, Remigijus; Danielienė, Jūratė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
In order to reveal the complementarity of business models, the factors that determine it in incoming tourism, and to prepare the conceptual model, the following discussion questions should be answered (the research problem is formulated by presenting questions in theoretical context): what is a business model and its structure?; what is business model complementarity?; what traits and identification characteristics are characteristic of it?; what factors determine business model complementarity in incoming tourism? The aim of the research – theoretically substantiate the traits and characteristics of business model complementarity and the factors that determine it in incoming tourism by preparing a conceptual model. Research methods: systematic analysis of scientific literature, comparative analysis. The key results of the research: the concepts and structures of a business model, complementarity and business model complementarity are defined by systematising conceptual insights, interorganizational relations and complementarity; according to the systemic point of view that explains the result of the interaction between an incoming tourism company business model and its structural elements, the conceptual model of business model complementarity and the factors that determine it in incoming tourism, are presented.